2017
DOI: 10.1177/1071100717709565
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Detection of Marginal Impaction in Supination-Adduction Ankle Fractures

Abstract: Level III, comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This special type of fracture has characteristics that other traditional ankle fractures do not have, as follows: 1) lateral collateral ligament injury; 2) subchondral bone and cartilage injury of the medial malleolus; 3) a horizontal lateral fracture line of the ankle and vertical fracture line of the medial malleolus; 4) a die-punch-like fragment of the medial malleolus evident on CT; and 5) injury to the articular surface of the distal tibia and vault collapse (Fig. 3 ).These features are not common in traditional rotational ankle fractures, but their important contribution to collapse is often ignored in clinical practice [ 6 , 7 , 15 ]. There is no accurate name for a type of fracture that involves the impaction of a medial triangular fragment on the lateral articular surface of the tibia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This special type of fracture has characteristics that other traditional ankle fractures do not have, as follows: 1) lateral collateral ligament injury; 2) subchondral bone and cartilage injury of the medial malleolus; 3) a horizontal lateral fracture line of the ankle and vertical fracture line of the medial malleolus; 4) a die-punch-like fragment of the medial malleolus evident on CT; and 5) injury to the articular surface of the distal tibia and vault collapse (Fig. 3 ).These features are not common in traditional rotational ankle fractures, but their important contribution to collapse is often ignored in clinical practice [ 6 , 7 , 15 ]. There is no accurate name for a type of fracture that involves the impaction of a medial triangular fragment on the lateral articular surface of the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…The talus impacts the medial plate of the tibia to cause oblique, oblique inward upward or vertical upward fractures combined with bone compression, collapse, or cartilage surface damage to the ankle vault due to serious damage to the ankle [ 5 ]. If the injury is not accurately diagnosed and treated with open anatomical reduction and internal fixation, loss of joint integrity may occur, resulting in severe traumatic sequelae, permanent ankle pain and greatly reduced quality of life [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supination-adduction (SA) fractures at stage II involve vertical or oblique fragmentation of the medial malleolus; although there is a high frequency of concurrent medial plafond involvement, estimated at 42% to 61% in stage II supination-adduction injuries, posterior malleolar fractures rarely occur. 1,43 A high-energy stage III supination–external rotation injury translates into the posterior aspect of the medial malleolar structures, causing either the PITFL to rupture or a posterior malleolar avulsion fracture to occur. Pronated-external rotation initially involves disruption of the deltoid ligament complex or medial malleolar fracture (stage I); further force may result in disruption of the anterior and posterior inferior tibiofibular ligaments or posterior malleolar avulsion fracture (stage II).…”
Section: Anatomy and Pathomechanicsmentioning
confidence: 99%
“…It is estimated that posterior malleolar fractures are found in 40% of rotational ankle fractures, but they may also occur in isolation, as a component of pilon fractures, or as a component of a distal tibia fracture. 1,6,31,33 These fractures involve both the weight-bearing portion of the tibial plafond and the ankle syndesmosis, thus affecting tibiotalar load transfer, as well as posterior talar and rotatory ankle stability. 3,46,49 Recent attention has focused on the workup and management of this heterogenous group of fractures and their relationship to ankle and distal tibia fracture outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of clinically meaningful articular impaction in SAD type II ankle fractures is largely unknown, although one recent series reports that impaction was noted intraoperatively half of the time and operatively addressed in 84% of these patients. 1,8,16 Furthermore, the influence of articular impaction and reduction quality on posttraumatic arthrosis remains understudied in these injuries. In a prior study, we reported that treatment failure was more common in pilon fractures compared with SAD ankle injuries and introduced the importance of anatomic restoration of the articular surface to optimize outcomes in these patients.…”
Section: Introductionmentioning
confidence: 99%